A Randomized Trial Comparing Cardiac Rehabilitation to Standard of Care for Adults With Congenital Heart Disease. Issue 2 (March 2018) - Opotowsky, Alexander R.; Rhodes, Jonathan; Landzberg, Michael J.; Bhatt, Ami B.; Shafer, Keri M.; Yeh, Doreen DeFaria; Crouter, Scott E.; Ubeda Tikkanen, Ana
Background: Cardiac rehabilitation (CR) improves exercise capacity and quality of life while reducing mortality in adults with acquired heart disease. Cardiac rehabilitation has not been extensively studied in adults with congenital heart disease (CHD). Methods: We performed a prospective, randomized controlled trial (NCT01822769) of a 12-week clinical CR program compared with standard of care (SOC). Participants were ≥16 years old, had moderate or severe CHD, had O2 saturation ≥92%, and had peak O2 consumption (V ̇ O 2 pk ) < 80% predicted. We assessed exercise capacity, physical activity, quality of life, self-reported health status, and other variables at baseline and after 12 weeks. The prespecified primary end point was change inV ̇ O 2 pk . Results: We analyzed data on 28 participants (aged 41.1 ± 12.1 years, 50% male), 13 randomized to CR and 15 to SOC.V ̇ O 2 pk averaged 16.8 ± 3.8 mL/kg/min, peak work rate = 95 ± 28 W, and median Minnesota Living with Heart Failure Questionnaire (MLHFQ) score = 27 (interquartile range: 11-44). Cardiac rehabilitation participants were older (48 ± 9 years vs 36 ± 12 years; P = .01), but there were no significant between-group differences in other variables. There were no adverse events related to CR.V ̇ O 2 pk increased in the CR group compared with SOC (+2.2 mL/kg/min, 95% confidence interval: 0.7-3.7; P = .002, age-adjusted +2.7 mL/kg/min; P = .004); there was a nonsignificant improvement in work rate (+8.1 W; P = .13). Among the 25 participants with baseline MLHFQ > 5, there was a clinically important >5-point improvement in 72.7% and 28.6% of CR and SOC participants, respectively ( P = .047). Cardiac rehabilitation was also associated with improved self-assessment of overall health ( P < .04). Conclusions: Cardiac rehabilitation is safe and is associated with improvement in aerobic capacity and self-reported health status compared with SOC in adults with CHD.